BARRIERS TO FAMILY PLANNING IN PAKISTAN - Imran, Muhammad; Yasmeen, Rehana (Journal of Ayub Medical College Abbottabad, 2020)
According to the last census conducted in Pakistan in 2017, Pakistan’s population reach up to 207.7 million and a growth rate of 2.4. Currently. Researchers and policymakers estimated that if the growth rate of Pakistan remains the same, then up till 2050, Pakistan becomes 5th most populous country in the world. Pakistan has a commitment of FP2020 that Pakistan will achieve a CPR rate of 55% at the national level, but it seems difficult to achieve as Pakistan Demographic Health Survey conducted during 2017-18 shows that overall contraceptive prevalence rate of Pakistan is 34%. In this review, we have identified barriers that can restrict the use of family planning, which includes: lack of knowledge and motivation, lack of agency, communication gap and limited availability and accessibility. There is a need to increase awareness and understanding of contraceptive methods, change negative attitudes and help couples to change their behaviours. The decision-maker should make such policies that can help in improving family planning usage and helps in population control. Keywords: Contraceptive; Family planning; Pakistan